2022
DOI: 10.3389/fnut.2022.1030583
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein improves flesh quality by enhancing antioxidant ability via the NF-E2-related factor 2/Kelch-like ECH-associated protein 1 signaling pathway in softshell turtle (Pelodiscus sinensis)

Abstract: An 8-week feeding trial was performed to assess the influence of a gradient of protein levels (14.38–45.23%) on flesh quality, skin color, amino acid profile, collagen, antioxidant capability, and antioxidant-related signaling molecule expression of the softshell turtle (Pelodiscus sinensis). Hardness, gumminess, chewiness, and yellowness values in the plastron and carapace, along with collagen, superoxide dismutase, catalase, total antioxidant capacity, and glutathione peroxidase, all improved with elevating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(59 reference statements)
2
0
0
Order By: Relevance
“…Six amino acids-glycine, glutamic acid, aspartic acid, tyrosine, phenylalanine, and alanine-are usually thought to contribute specifically to food deliciousness. It has been shown that optimal dietary protein could improve the flavor of muscle by changing the content of free amino acids [2,25]. The overall flesh flavor amino acids were increased with dietary protein inclusion levels 38-41% in triploid crucian carp, which was consistent with a previous study in which the content of free glutamate and glycine in muscles increased linearly with dietary protein inclusion levels [26].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Six amino acids-glycine, glutamic acid, aspartic acid, tyrosine, phenylalanine, and alanine-are usually thought to contribute specifically to food deliciousness. It has been shown that optimal dietary protein could improve the flavor of muscle by changing the content of free amino acids [2,25]. The overall flesh flavor amino acids were increased with dietary protein inclusion levels 38-41% in triploid crucian carp, which was consistent with a previous study in which the content of free glutamate and glycine in muscles increased linearly with dietary protein inclusion levels [26].…”
Section: Discussionsupporting
confidence: 89%
“…The organism always maintains its health by strengthening the antioxidant system's defense to deal with ROS produced by protein metabolism and prevents oxidative damage to muscle cells. Previous studies reported that the antioxidant system was enhanced mainly by upregulating the mRNA expressions of genes, such as GSH, GST, and GPX, increasing the activity of enzymes, such as SOD and GSH, for scavenging oxidative metabolites ROS and MDA [25,31]. In this study, GPX genes (GPX1 and GPX4α) expression showed a similar tendency to reach the peak in the 32% dietary protein inclusion group.…”
Section: Discussionsupporting
confidence: 67%